2019
DOI: 10.3390/molecules24030610
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Saccharomyces cerevisiae Yeast and Lactic Acid Bacteria in the Formation of 2-Propanol from Acetone during Fermentation of Rye Mashes Obtained Using Thermal-Pressure Method of Starch Liberation

Abstract: This study set out to assess the acetone content in rye sweet mashes prepared using the thermal-pressure method of starch liberation, and to investigate the formation of 2-propanol during the fermentation process. In the first set of experiments, we evaluated the correlation between the color and the content of acetone and furfural in industrially produced sweet mashes (n = 37). The L * value was negatively correlated with the content of both acetone and furfural, while chromatic parameters a * and b * and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The color parameters (L*, a*, b*) were measured using a LabScan XE System (Hunter Associates Laboratory, Inc., Reston, VA, USA) colorimeter by triplicate using a CIELAB system. Instrumental color was expressed as the Hue angle (Equation (1)), Chroma (Equation (2)), and Yellowness Index (YI, Equation (3); [ 28 ]). Evaluation of viscosity was determined in triplicates using a rheometer (MCR 302, Anton Paar Canada Inc, Quebec, Canada) at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The color parameters (L*, a*, b*) were measured using a LabScan XE System (Hunter Associates Laboratory, Inc., Reston, VA, USA) colorimeter by triplicate using a CIELAB system. Instrumental color was expressed as the Hue angle (Equation (1)), Chroma (Equation (2)), and Yellowness Index (YI, Equation (3); [ 28 ]). Evaluation of viscosity was determined in triplicates using a rheometer (MCR 302, Anton Paar Canada Inc, Quebec, Canada) at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…cerevisiae in co-culture led to an increase of 2-phenylethanol content in wine, conversely mixed-cultures with C. zemplinina and S. cerevisiae have shown a lower concentration of this compound, together with other alcohols [44,45]. Alcohols, such as 2-phenylethanol, are synthesized by the yeast from amino acids and/or simple sugars [46,47]. It is possible to speculate that the specific combination of Lactobacillus plantarum/Saccharomyces cerevisiae/Candida zemplinina strains might have boosted the concentration of a specific precursor.…”
Section: Lab-scale Trialsmentioning
confidence: 99%
“…However, there is nothing in the literature that proves whether acetone, which occurs in sweet mashes as a product of the thermal-pressure treatment of cereal grains, can be a source of isopropyl alcohol synthesis during ethanol fermentation in the presence of yeast and/or bacteria. In our previous research [18], we observed that acetone content decreased during fermentation of mashes using S. cerevisiae and LAB separately. The decrease in acetone content was accompanied by the appearance of propan-2-ol in the fermented mashes, perhaps indicating that both yeast and LAB are responsible for the reduction of this ketone to isopropyl alcohol.…”
Section: Resultsmentioning
confidence: 96%
“…A number of microorganisms, especially anaerobic bacteria, are able to synthetize isopropyl alcohol [4,19]. This secondary alcohol may be found in distillery mashes [18], as well as in distillates [3]. However, there is nothing in the literature that proves whether acetone, which occurs in sweet mashes as a product of the thermal-pressure treatment of cereal grains, can be a source of isopropyl alcohol synthesis during ethanol fermentation in the presence of yeast and/or bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation